Impact of vernalization on flowering, fruiting, and yield of strawberry (Fragaria × ananassa) cultivars under tropical highland conditions - EDGEL O. ESCOMEN; GERLIE S. JAMBARO (Asian Journal of Agriculture, 2026)
Abstract. Escomen EO, Jambaro GS. 2026. Impact of vernalization on flowering, fruiting, and yield of strawberry (Fragaria × ananassa) cultivars under tropical highland conditions. Asian J Agric 10 (1): g100116. https://doi.org/10.13057/asianjagric/g100116. Vernalization is a key physiological process influencing flowering, fruiting, and yield in strawberry, yet its effectiveness varies among cultivars, particularly under tropical highland conditions where natural chilling is limited. This study examines the performances of vernalization in terms of phenology, productivity, and fruit characteristics of five strawberry cultivars, namely Albion, Snow White, Summer Princess, Sweet Charlie, and Sweet Honeoye. The experiment was conducted in the tropical highland environment in Marawi City, Philippines, to improve strawberry production in tropical and subtropical areas. A 2x5 split-plot in Randomized Complete Block Design (RCBD) with vernalization (3°C for 10 h before planting) as the main plot and cultivar as the subplot. Vernalization significantly accelerated flowering, increased flower and fruit numbers, and enhanced total yield across cultivars (p<0.05). Vernalized plants produced a higher mean yield (10.83 t ha-¹) compared with non-vernalized plants (7.38 t ha-¹), primarily due to increased reproductive output. Sweet Honeoye and Sweet Charlie produced 13.68 t ha-1 and 13.47 t ha-1, respectively. The number of flower formations was greater, as Sweet Honeoye generated up to a mean of 40.25 flowers per plant. The fruit yield was also increased, especially in Sweet Honeoye and Sweet Charlie. The number of runners was reduced due to vernalization, which was most significant with Albion. Snow White experienced an increase in the Total Soluble Solids (TSS) to 15.35°Brix. Each cultivar has a different response to vernalization. Significant interaction effects between vernalization and cultivar were observed for key phenological and yield traits, underscoring genotype-specific responses. These findings demonstrate that short-duration vernalization can substantially improve strawberry productivity in tropical highlands when matched with responsive cultivars, offering a practical strategy for enhancing yield stability under warm-climate conditions.